2021
DOI: 10.1159/000511711
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Possible Mechanism of Endoscopic Vidian Neurectomy for House Dust Mite-Sensitive Allergic Rhinitis

Abstract: <b><i>Background/Aims:</i></b> Endoscopic vidian neurectomy (EVN) for allergic rhinitis (AR) has good clinical effects. However, the pathophysiological basis of the effect of EVN on AR is still poorly understood. This study aimed to investigate the efficacy of EVN on house dust mite (HDM)-sensitive AR and the dynamic changes of serum immunoglobulin E and some immune regulatory factors. <b><i>Methods:</i></b> Twenty HDM-sensitive AR patients were treated with bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Evidence published from 2011 onwards provides support regarding its use in AR patients. Observational studies and a non‐randomized controlled trial found that AR patients experienced improvements in sneezing, nasal discharge, obstruction, itching, and QOL 2375,2387–2390 . An RCT and another non‐randomized controlled trial of patients with both AR and CRSwNP found similar results, as well as improvement on pulmonary functions tests 2391,2392 .…”
Section: Managementmentioning
confidence: 89%
“…Evidence published from 2011 onwards provides support regarding its use in AR patients. Observational studies and a non‐randomized controlled trial found that AR patients experienced improvements in sneezing, nasal discharge, obstruction, itching, and QOL 2375,2387–2390 . An RCT and another non‐randomized controlled trial of patients with both AR and CRSwNP found similar results, as well as improvement on pulmonary functions tests 2391,2392 .…”
Section: Managementmentioning
confidence: 89%